2008
DOI: 10.1002/jpln.200700073
|View full text |Cite
|
Sign up to set email alerts
|

Subsoil properties and cereal growth as affected by a single pass of heavy machinery and two tillage systems on a Luvisol

Abstract: Compared to moldboard plowing, conservation tillage is frequently discussed to alleviate soil stresses caused by high wheel loads and, thus, decrease the risk of subsoil compaction. On a Luvisol derived from loess (Göttingen, Lower Saxony, Germany), a wheeling experiment was conducted in two contrasting tillage systems (continuous moldboard plowing [MP] 30 cm deep and shallow mixing [SM] 10 cm deep). A six‐row self‐propelled sugar beet tanker harvester (SBH 6: 34–36 Mg total vehicle weight, 8–11 Mg wheel load,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Spekken et al (2015) suggested that row length must be at least 30 m to be economically profitable to manage in field operations for sugarcane (Saccharum officinarum L.). Other studies suggest it is better to operate with maximum pass efficiency than to repeatedly drive over the same area (Arvidsson, Bölenius, & Cavalieri, 2012;Heuer, Tomanová, Koch, & Märländer, 2008). Though controlled traffic farming is proven to reduce the impact of compaction (Marinello et al, 2017), it is not a common practice for corn silage or grain production in New York.…”
mentioning
confidence: 99%
“…Spekken et al (2015) suggested that row length must be at least 30 m to be economically profitable to manage in field operations for sugarcane (Saccharum officinarum L.). Other studies suggest it is better to operate with maximum pass efficiency than to repeatedly drive over the same area (Arvidsson, Bölenius, & Cavalieri, 2012;Heuer, Tomanová, Koch, & Märländer, 2008). Though controlled traffic farming is proven to reduce the impact of compaction (Marinello et al, 2017), it is not a common practice for corn silage or grain production in New York.…”
mentioning
confidence: 99%
“…(1) Koch and Märländer show two figures in their comment presenting air-conductivity and saturated-hydraulic conductivity values both from own measurements (Heuer et al, 2008) and from Fazekas (2005). The air-conductivity values they show citing Fazekas (2005) are all >150 cm s -1 which is incorrect.…”
mentioning
confidence: 99%